Determination of the efficacy of anthelmintics used in the control of gastrointestinal nematodes of goats from Tucumán, Argentina (FAVE Sección Ciencias Veterinarias, 2020)
Almost 93% of goat production in Argentina is developed by small farmers, who generally use anthelmintics without professional advice, which has led to the development of resistance, seriously compromising the sustainability of nematode control. This study aims to determine the efficacy of ivermectin, albendazole and levamisole for the treatment of verminous gastroenteritis in four groups of eight goats each, using the Faecal Egg Count Reduction Test (FECRT). The results showed a 100% reduction in the number of EPG for the groups treated with albendazole and levamisole and a 17% reduction for the group treated with ivermectin, compared to the control group, which allows us to infer that there is resistance to this drug.
Keywords: goats; verminous gastroenteritis; resistance; ivermectin